Contralateral effect of systemic absorption of low dose bevacizumab (Avastin) after unilateral intravitreal injection in severe retinopathy of prematurity (ROP) - Shafiq, Ayad (BMJ Case Rep, 2020)
An extremely premature baby boy born at 23 weeks’ gestational age was treated with unilateral low dose of 0.16 mg/0.025 mL intravitreal bevacizumab in the left eye for aggressive retinopathy of prematurity (ROP). He developed photographically documented changes in his contralateral right eye on imaging 5 days later. Second eye treatment was at 12 days. He has development assessment and ophthalmic review beyond age 2, which is normal. Systemic absorption of the drug caused an end organ effect to slow down and reverse ROP in his untreated right eye. Both eyes vascularised fully. His normal Bayley III developmental score at age 2 is uncommon for a 23-week gestation baby. Even at a low dose, bevacizumab has the potential for end organ effect on the second eye, and therefore other organs. In this case, there are no medium-term measurable neurodevelopmental side-effects. We suggest longer term follow-up is required before excluding unwanted side-effects.